Acyl Quinic Acid Derivatives Screened Out from Carissa spinarum by SOD-Affinity Ultrafiltration LC-MS and Their Antioxidative and Hepatoprotective Activities - Ye Liu; Felix Wambua Muema; Yong-Li Zhang; Ming-Quan Guo (MDPI AG, 2021)
Carissa spinarum Linn. has been utilized both in the food industry and as a traditional medicine for various ailments, while the responsible chemical components and action mechanisms of its antioxidative and hepatoprotective activities remain unclear. In this work, at least 17 quinic acid derivatives as potential ligands for the superoxide dismutase (SOD) enzyme from Carissa spinarum L. were screened out using the bio-affinity ultrafiltration with liquid chromatography mass spectrometry (UF-LC/MS), and 12 of them (1-12), including, three new ones (1-3), were further isolated by phytochemical methods and identified by high resolution electrospray ionization mass spectrometry (HR-ESI-MS) and extensive nuclear magnetic resonance (NMR) spectroscopic analysis. All of these isolated compounds were evaluated for their antioxidant activities by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric-reducing antioxidant power (FRAP) methods. As a result, compounds 4 and 6-11 displayed similar or better antioxidant activities compared to vitamin C, which is in good agreement with the bio-affinity ultrafiltration with SOD enzyme. Then, these compounds, 4 and 6-11, with better antioxidant activity were further explored to protect the L02 cells from H2O2-induced oxidative injury by reducing the reactive oxygen species (ROS) and Malondialdehyde (MDA) production and activating the SOD enzyme. To the best of our knowledge, this is the first report to use an efficient ultrafiltration approach with SOD for the rapid screening and identification of the SOD ligands directly from a complex crude extract of Carissa spinarum, and to reveal its corresponding active compounds with good antioxidative and hepatoprotective activities.